The Transformation of Furniture Craft Shape in Tempel Lemahbang Village, Blora in Facing Market Development - Dwiningtyas, Ratih; Triyanto, Triyanto; Syakir, Syakir (Universitas Negeri Semarang, 2018)
The transformation of furniture craft shape in Tempel village Lemahbang is done by the craftsmen to face the market development. This research aims at understanding the transformation of furniture craft shape in Tempel village Lemahbang Blora in facing market development. The research method was qualitative while the data collection technique used observation, interview, document study. The technique of data validity used source triangulation, while the data analysis procedure used data reduction, data presentation, and conclusion drawing. The research result is that the furniture transformation happened from the shape and material. The shape aspect transformation is from classical furniture, such as wooden table or chair in Perancisan (French) style to rustic style. The rustic shape of furniture has created tables, chairs, and ornamental animal shaped furniture. The rustic furniture created by the craftsman has rough shape, preserve natural characteristic from the material used, i.e, bonggol (part of Jati tree’s root). The research findings show that the furniture crafts in Blora experience shape transformation to keep up with market development. The benefit of the research for arts education especially formal arts education agency is as a source of arts teaching learning based on local culture. The suggestion for the craftsmen is always to develop their self-potential, especially their English competency so that they will be easy to communicate with foreign customers.